2018
DOI: 10.1029/2018tc004997
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal and Longitudinal Patterns of Exhumation in the Andes of North‐Central Chile

Abstract: New thermochronometric data provide evidence for an along‐strike diachronous building of the Andes in north‐central Chile (28.5–32°S). Geochronological (U‐Pb zircon) and thermochronological (apatite fission track and (U‐Th)/He) analyses of rock units were obtained in west‐to‐east transects across the western topographic front. Thermal models indicate that the area west of the topographic front was little exhumed since approximately 45 Ma. To the east of the western topographic front, the Main Cordillera shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 86 publications
3
22
0
Order By: Relevance
“…Similar to the northern segment, exhumation during the Paleogene is recorded with relatively low rates (< 0.2 km/Ma) although data resolution is too low to infer changes in exhumation rates. This supports previous interpretations of structural and sedimentary observations (Martínez et al, 2016;Rossel et al, 2016;Fosdick et al, 2017;Martínez et al, 2018) and thermochronological data (Cembrano et al, 2003;Lossada et al, 2017;Rodríguez et al, 2018) that indicate an early, pre-Oligocene onset of mountain building in this part of the Andes. In the Oligocene, contractional deformation was interrupted by extension and only resumed in the early Miocene by basin inversion and deformation in the Frontal Cordillera ( Fig.…”
Section: Central Segment (28 -32°s)supporting
confidence: 90%
See 1 more Smart Citation
“…Similar to the northern segment, exhumation during the Paleogene is recorded with relatively low rates (< 0.2 km/Ma) although data resolution is too low to infer changes in exhumation rates. This supports previous interpretations of structural and sedimentary observations (Martínez et al, 2016;Rossel et al, 2016;Fosdick et al, 2017;Martínez et al, 2018) and thermochronological data (Cembrano et al, 2003;Lossada et al, 2017;Rodríguez et al, 2018) that indicate an early, pre-Oligocene onset of mountain building in this part of the Andes. In the Oligocene, contractional deformation was interrupted by extension and only resumed in the early Miocene by basin inversion and deformation in the Frontal Cordillera ( Fig.…”
Section: Central Segment (28 -32°s)supporting
confidence: 90%
“…are Paleogene and, with one exception (Rodríguez et al, 2018), no ages younger than 10 Ma are observed (Fig. 7).…”
Section: Exhumation History Of the Central Andesmentioning
confidence: 94%
“…These AHe ages define a younger cooling episode than the results from Los Pelambres‐Pachón but coincide with (1) a ~7 Ma AHe age obtained near the northern termination of the Pocuro fault (~45 km northwest of this study's sample locations); (2) thermal models that indicate ~7 Ma rapid cooling in the western Frontal Cordillera at 30°S; and (3) numerous ~8–2 Ma AHe and apatite fission track cooling ages from the Western Principal Cordillera at 33–35°S (Farías et al, 2008; Maksaev et al, 2009; McInnes et al, 2005; Piquer et al, 2017; Rodríguez et al, 2018). Regional late Miocene–Pliocene cooling ages consistently postdate the emplacement of magmatic or hydrothermal systems by at least several million years and point to a major episode of tectonic exhumation and surface uplift that affected the Andean hinterland from ~30°S to 35°S (Farías et al, 2008; Maksaev et al, 2009; Maydagán et al, 2020; Piquer et al, 2017; Rodríguez et al, 2018). At 32°S, seismicity beneath the hinterland and retroarc domains suggests contractional deformation is still active at depth (<10–20 km; Ammirati et al, 2015; Gregori & Christiansen, 2018; Marot et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…The southern Central Andes (31–33°S; Figure 1a) define type examples of Cordilleran orogenesis during Neogene flattening of the subducted oceanic plate, but debate persists regarding (1) the timing of shortening‐induced exhumation along basement‐involved ranges in the Frontal Cordillera hinterland domain (Figure 1b) and (2) the geometry of nonemergent structures, and potential structural linkages, between the retroarc hinterland and flanking fold‐thrust belt. Previous studies have proposed a range of late Eocene–late Miocene ages for initial shortening and uplift of the Frontal Cordillera (~35 Ma, Lossada et al, 2017; ~25 Ma, Hoke et al, 2015; 24–17 Ma, Levina et al, 2014; 20–17 Ma, Buelow et al, 2018; Pinto et al, 2018; ~14–12 Ma, Jordan et al, 1996; Perez, 1995; ~9 Ma, Ramos & Folguera, 2009; 7 Ma, Rodríguez et al, 2018). Interpretations of regional structures that accommodate crustal thickening and transfer shortening from lower to upper crustal levels remain largely schematic and are complicated by limited exposures near the transition from basement‐involved to thin‐skinned deformation (Figures 1b, 2; Allmendinger et al, 1990; Allmendinger & Judge, 2014; Cristallini & Ramos, 2000; Ramos et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation